Study on the zeta potential effect of Artocarpus heterophyllus natural-based coagulant in wastewater treatment - Priyatharishini, Mardarveran; N. M., Mohktar (IOP Publishing, 2020)
The application of chemical coagulants which is damaging to environment and human health has triggered to the exploration of new coagulants from natural based sources. This study emphasized on the performance of a treatment process to remove particles in the synthetic domestic wastewater by coagulation using Artocarpus heterophyllus (jackfruit) peel extract and evaluation of zeta potential (ζ). The measurement of zeta potential which is the criteria defining the electrostatic interaction between pollutants and natural coagulant agent is used in proposing mechanism of coagulation. The jar test experiment was carried out and the treated wastewater was analysed to determine reduction in turbidity, BOD, COD and TSS. The coagulant extracts were characterized in terms of surface charge. The best operating conditions were: pH 2 and dosage 60 mg/L. The corresponding removal efficiencies for turbidity, TSS, COD and BOD were 80 %, 70 %, 46 % and 20 % respectively. The measured zeta potential of the coagulant was -25.2 mV at its original pH, 6.95. On the other hand, the surface charge of synthetic wastewater was positive at pH 2 and later turned to be negative as the pH is increased up to pH 12. This best describes that jackfruit peel coagulant possessed the characteristic of anionic polyelectrolytes which involves bridging mechanism. The results obtained here suggest that coagulation using Artocarpus heterophyllus peel extract can be employed as an effective and low-cost preliminary technique in wastewater treatment process.